Collaborating in healthcare delivery: exploring conceptual differences at the "bedside". Issue 2 (March 2015) - Barrow, Mark; McKimm, Judy; Gasquoine, Sue; Rowe, Deborah
Abstract Calls for greater collaboration amongst health professionals and for programmes to support this are not new, nor are they likely to diminish. While various interventions have been adopted to improve collaboration, the literature suggests that these have neither been well-informed with a strong conceptual base nor have they accounted for the context in which the health professionals work. In this study, interviews of senior doctors and nurses in two hospital-based services explored experiences of interprofessional collaboration and the processes involved. A framework based on activity theory was used to analyse the data. The data suggest a dichotomy between nurses as collectivist, protocol and systems-driven and doctors as individualist and autonomy-driven, although this played out differently in each service. Unless such complexities and contextual factors are addressed in the preparation for collaboration it will continue to fall short.